Students' Mathematical Literacy in Solving PISA Problems Observed by Learning Styles - Rivai, Ahmad; Lestari, Alia; Munir, Nilam Permatasari; Anas, Aswar (Mathematics Education Journal, 2023)
Mathematical literacy helps an individual recognize the role or use of mathematics in everyday life. One of the factors supporting mathematical literacy is the learning style of the student. This study aimed to describe the mathematical literacy of students in the context of SMP Negeri 1 Palopo based on their answers to PISA test questions by observing their learning styles. The subjects in this study were three eighth graders each representing visual, auditory, and kinesthetic learning styles. The data instruments used were a learning style questionnaire, a mathematical literacy test based on the 2012 PISA test draft, and an interview guide. The results of the learning style questionnaire were analyzed by referring to the indicators of the three learning styles under study, while the results of the PISA test were analyzed by referring to the indicators for each PISA level. The results of this study indicated that the visual student and the auditory student had mathematical literacy at level 3 as shown by their ability to connect and reflect things involved in interpretation and basic reasoning, while the kinesthetic student had mathematical literacy at level 4 as shown by their ability to build and communicate explanations and argumentation based on interpretations, arguments, and actions. Based on the research results, it is suggested that students be accustomed to working on PISA-like problems to improve their mathematical literacy. DOI: https://doi.org/10.22342/jpm.17.1.19905.121-134